1997
DOI: 10.1144/gsjgs.154.6.1021
|View full text |Cite
|
Sign up to set email alerts
|

Regional tectonic setting of Hong Kong: implications of new gravity models

Abstract: Hong Kong lies on the SE margin of the Cathaysia Block and straddles the NE-trending Lianhuashan Fault Zone, one of the dominant structural features of SE China. Isotope signatures of the Mesozoic granites have indicated that the zone overlies a major crustal discontinuity. The proposed gravity model of Hong Kong consists of a heterogeneous upper crust underlain by middle to lower crust composed of a felsic Archaean segment, approximately 25 km wide, flanked by more mafic Proterozoic crust. The southern bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
4
17
0
Order By: Relevance
“…The maximum amplitude minima are located in the Shenzhen Bay caused by a thick pile of sediments. Values close to the southern boundary are well consistent with those derived from Hong Kong gravity data (Fletcher et al, 1997). …”
Section: Bouguer Gravity Anomaliessupporting
confidence: 86%
See 1 more Smart Citation
“…The maximum amplitude minima are located in the Shenzhen Bay caused by a thick pile of sediments. Values close to the southern boundary are well consistent with those derived from Hong Kong gravity data (Fletcher et al, 1997). …”
Section: Bouguer Gravity Anomaliessupporting
confidence: 86%
“…It indicates that the fault zone has extended into the lower crust or even the upper mantle. The deep crustal discontinuity is confirmed by other geophysical studies (Xie et al, 1997;Fletcher et al, 1997;Sewell et al, 2000). The recent crustal structure from deep seismic sounding shows that a high-velocity (7.1-7.4 km/s) layer in lower crust is absent in the study area (Li et al, 2006).…”
Section: Tectonic and Geological Settingsupporting
confidence: 78%
“…This implies that the lithosphere extension may have been active since the Middle Jurassic. Pulses of rapid extension during the Late Jurassic are also reported from the Hong Kong region (Fletcher et al 1997). The Upper Triassic-Cretaceous extensional basins, such as the Shiwandashan basin in SE Guangxi (Gilder et al 1996), mostly developed on the Palaeozoic to Middle Triassic basement that was ubiquitously folded by the Indosinian Orogeny (Li 1998).…”
Section: Tectonic Implicationsmentioning
confidence: 86%
“…High precision U-Pb zircon dating of Middle and early Late Jurassic volcanic rocks, plutons and dykes (Davis et al, 1997) constrain the timing of terrane amalgamation to between approximately 164 and 161 Ma followed shortly afterward by a pulse of plutonism. The Tolo Terrane coincides with isotopically distinct basement sources of Hong Kong granitoids which are reflected by regional gravity models (Fletcher et al, 1997).…”
Section: Late Mesozoic Tectonic Model For Se Chinamentioning
confidence: 65%
“…Darbyshire and Sewell (1997) Busby and Langford (1995). Modeling of the regional gravity data by Fletcher et al (1997) revealed contrasting densities in the basement consistent with a felsic Archean crust in the northwest separating denser blocks of mafic Proterozoic crust in the southeast. The gravity map of the region around Hong Kong and neighbouring Guangdong Province compiled by Fletcher et al (2004) shows a prominent NE-trending gradient in Bouguer anomaly values extending along the coast consistent with the pattern observed in Hong Kong.…”
Section: Geological Settingmentioning
confidence: 94%